Emergence of carbapenem‐resistant Klebsiella pneumoniae species complex from agrifood systems: detection of ST6326 co‐producing KPC‐2 and NDM‐1 - Furlan, João Pedro Rueda; Silva Rosa, Rafael; Ramos, Micaela Santana; Santos, Lucas David Rodrigues; Savazzi, Eduardo Angelino; Stehling, Eliana Guedes (Journal of the science of food and agriculture, 2024)
Background Klebsiella pneumoniae species complex (KpSC) is an important disseminator of carbapenemase‐encoding genes, mainly blaKPC‐2 and blaNDM‐1, from hospitals to the environment. Consequently, carbapenem‐resistant strains can be spread through the agrifood system, raising concerns about food safety. This study therefore aimed to isolate carbapenem‐resistant KpSC strains from the agricultural and environmental sectors and characterize them using phenotypic, molecular, and genomic analyses. Results Klebsiella pneumoniae and Klebsiella quasipneumoniae strains isolated from soils used for lemon, guava, and fig cultivation, and from surface waters, displayed an extensive drug‐resistance profile and carried blaKPC‐2, blaNDM‐1, or both. In addition to carbapenemase‐encoding genes, KpSC strains harbor a broad resistome (antimicrobial resistance and metal tolerance) and present putative hypervirulence. Soil‐derived K. pneumoniae strains were assigned as high‐risk clones (ST11 and ST307) and harbored the blaKPC‐2 gene associated with Tn4401b and Tn3‐like elements on IncN‐pST15 and IncX5 plasmids. In surface waters, the coexistence of blaKPC‐2 and blaNDM‐1 genes was identified in K. pneumoniae ST6326, a new carbapenem‐resistant regional Brazilian clone. In this case, blaKPC‐2 with Tn4401a isoform and blaNDM‐1 associated with a Tn125‐like transposon were located on different plasmids. Klebsiella quasipneumoniae ST526 also presented the blaNDM‐1 gene associated with a Tn3000 transposon on an IncX3 plasmid. Conclusion These findings provide a warning regarding the transmission of carbapenemase‐positive KpSC across the agricultural and environmental sectors, raising critical food safety and environmental issues. © 2024 Society of Chemical Industry.